Profil Komposisi Kimia Dan Senyawa Bioaktif Nira Aren (Arenga Pinnata) Serta Turunannya: Tinjauan Dekade Terakhir: Chemical Composition and Bioactive Compounds of Palm (Arenga Pinnata) Sap And Its Derivatives: A Review Of The Last Decade - Reza Arianto Sultan; Miftahuddin; Aidil Zulhaq Paradiman; Mentari Mangguali; Abdi Wahid Kurniawan; Nurul Al Varqani (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2026)
ABSTRACT Palm sap (Arenga pinnata) plays a strategic role in the agro-industrial sector; however, its utilization is frequently constrained by rapid microbiological degradation.This review synthesizes research advancements over the past decade (2015-2025) to characterize the chemical properties, nutritional profiles, and bioactive potential of palm sap and its derivatives. Employing a narrative review of literature from reputable databases, this study identifies palm sap as a complex biochemical system rich in sucroses, essential amino minerals (K, Mg, Ca, and P), vitamins, and a comprehensive profile of amino acids. The identification of phenolic and flavonoid constituents further substantiates its potential as a significant source of natural antioxidants. This review highlights that the retention of these functional compounds is highly dependent on the precision of processing techniques. The implementation of vacuum evaporation and advanced drying technologies, such as spray drying and freeze-drying, has proven superior in preserving the integrity of thermolabile bioactive compounds compared to conventional open-pan heating. In conclusion, a comprehensive understanding of biochemical stability dynamics during processing provides a critical foundation for innovation and the downstream development of sugar palm commodities, facilitating the production of value-added and globally competitive functional foods. Keywords: Antioxidant activity, Arenga pinnata, Bioactive compounds, Palm sap, Thermal stability.